Consumers' Perceived Interactivity & Intention to Use Mobile Banking in Structural Equation Modeling - Krishanan, Darmesh; Khin, Aye Aye; Teng, Kevin Low Lock; Chinna, Karuthan (International Review of Management and Marketing, 2016)
A fair amount studies has been carried out on mobile banking adoption but limited number of studies focused on perceived interactivity. In reality, literatures on the key motivations of the intention to use mobile banking are no common standard of measurement. Therefore, there is a need to evaluate the factors influencing the Malaysian consumers' intention to use mobile banking services. This research fills the gap by integrating Technology Acceptance Model with perceived risk, perceived cost and perceived interactivity aspects are incorporated. This study's foremost ambition is to analyze empirically the Malaysian consumers' intention to use mobile banking services via Structural Equation Modeling Approach. The findings indicated usefulness, perceived cost, perceived interactivity, perceived risk, relative advantage and easefulness are significant determinants of consumers' attitude towards using mobile banking which effects the consumers' intention to use mobile banking. A critique of the destiny of mobile banking concludes this paper. Keywords: Consumers' perceived interactivity, Mobile banking usage, Structural Equation Modeling Approach JEL Classifications: G21; M31; O33